Establishment of a stellate ganglion regulation model in mice using infrared polarized light irradiation - Zhao, Kaixuan; Zhang, Haoyue; Liu, Yanbo; Zhou, Ying; Zhi, Juan; Wang, Qianyu; Yang, Dong (Frontiers in Physiology, 2025)
ObjectiveTo explore the feasibility of establishing a mouse stellate ganglion (SG) regulation model through infrared polarized light (IPL) irradiation of the SG, and preliminarily evaluate its effects on SG function and related physiological indicators. Surgery, and IPL groups, with 8 mice in each group. A ZZIR-ID therapeutic device was used to directly irradiate bilateral SG regions of IPL group mice, with wavelength 980 nm, power density 1000 mW/cm2, 10 min per session (5 min per side), every other day for 6 times. The control group received no treatment, while the.ResultsCompared with the control and Sham surgery groups, the incidence of Horner’s syndrome in the IPL group increased significantly (P < 0.05), manifesting as bilateral ptosis and enophthalmos, lasting about 2 h. Immediately after treatment, eye temperature in the IPL group increased significantly compared to pre-treatment (P < 0.05). Heart rate in the IPL group decreased significantly 30 min post-treatment compared to pre-treatment (P < 0.01), lasting 1–2 h. There was no statistically significant difference in weight changes between groups (P > 0.05). In all treated mice, the characteristic signs of Horner’s syndrome developed within minutes of starting IPL exposure, reached their peak intensity between 1.5 and 2.5 h, and resolved completely within 3–4 h of the 10-min irradiation session.ConclusionIPL irradiation of SG can effectively induce Horner’s syndrome in mice, elevate eye temperature, and reduce heart rate. These findings suggest IPL as a potential method for modulating SG activity in preclinical models.